Pengujian Alat Pembangkit Listrik Tenaga Surya Solar Cell Sederhana - Sibuk Ginting; Jusuf Halawa; Libianko Sianturi; Richard A M Napitupulu (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2019)
One of the sources of electricity technology is solar cell. in principle solar cell converts solar energy into electrical energy, here a simple solar cell made of copper that is designed simply with copper material containing oxide is made into the negative side of the solar cell and positive as a copper palat which does not contain oxide / is not baked on electric stove in the design of this simple solar cell where the copper cross section area containing oxide with a size of 25cm x 30cm and the size of copper plate that does not contain oxide with U-shaped is 29cm x 32cm and coated with glass as a reflector with a size of 32cm x 34cm where in solar design This simple cell was conducted for 2 days during a solar cell experiment for 2 days with the highest voltage of 4.4 V, which is on the first day and the voltage on the second day gets the highest voltage of 4.0 V with the intensity different light.